1996
DOI: 10.1063/1.871654
|View full text |Cite
|
Sign up to set email alerts
|

Study of microinstabilities in toroidal plasmas with negative magnetic shear

Abstract: The micreinstabilities driven by a pardel velocity shear, and a temperature gradient of ions are studied in toroidal plasmas with negative magnetic shear. Both the fluid and the gyrekinetic formulations are investigated. It is found that for a broad range of parameters, the linear growth rates of the modes are lower, and the threshold temperature gradient q k is higher €or plasmas with negative magnetic shear compared to plasmas with p'ositive magnetic shear of equal magnitude. The reduction in the growth rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

1997
1997
2004
2004

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 15 publications
(5 reference statements)
0
19
0
Order By: Relevance
“…There are numerous papers which discuss the linear theory of weak-shear ITG modes, 1,15,[17][18][19] but none that we are aware of analyze the s→0 limit of the toroidal ITG. In fact, for sϭ0, the toroidal ITG has a finite growth rate, and the corresponding eigenfunction is a complex Mathieu function.…”
Section: A Effect Of Shear On Linear Flux-tube Eigenvaluesmentioning
confidence: 98%
See 1 more Smart Citation
“…There are numerous papers which discuss the linear theory of weak-shear ITG modes, 1,15,[17][18][19] but none that we are aware of analyze the s→0 limit of the toroidal ITG. In fact, for sϭ0, the toroidal ITG has a finite growth rate, and the corresponding eigenfunction is a complex Mathieu function.…”
Section: A Effect Of Shear On Linear Flux-tube Eigenvaluesmentioning
confidence: 98%
“…Following the notation of Ref. 18, we write the eigenvalue equation as b͑ ͒ϭ ͩ qk ⑀ n ͪ 2 2⑀ n , ͑B3͒…”
Section: Appendix B: Local Analysis Of Weak Shear Modesmentioning
confidence: 99%
“…Comparing the growth rates at the same absolute value ͉ŝ͉, the negative shear ŝ Ͻ0 gives smaller growth rates than the positive shear ŝ Ͼ0 within the range ͉ŝ͉Ͻ1.7, which is the same tendency as found in other works. 18,19 However, the critical values of ŝ , which give ␥ϭ0, have almost the same absolute value ͉ŝ͉ϳ1.7. We should note that validity of the ballooning representation is lost in the limit ŝ˜0 although the growth rate and real frequency for ŝ ϭ0 is plotted in Fig.…”
Section: Numerical Solution For Stable and Unstable Normal Modesmentioning
confidence: 99%
“…The effects of negative magnetic shear on ITG modes have been theoretically investigated by several authors 18,19 relation to improvement of core plasma confinement observed in large tokamaks. [20][21][22] However, the results in these works only showed the dependence of positive growth rates on the magnetic shear.…”
Section: Numerical Solution For Stable and Unstable Normal Modesmentioning
confidence: 99%
“…The growth rate is a maximum at sϭ 1 2 as can be understood from the small expansion of D i ( ,s). Dong et al (1996) re-investigate the somewhat subtle issue of the conditions for the existence of two distinct unstable drift modes: the eta-i (ITG) and the trapped electron (TE) mode. This is the standard case assumed for example in the Weiland transport model implemented in the Bateman-Kinsey transport codes (Kinsey et al, 1996).…”
Section: Reversed Magnetic Shear and The Hybrid Trapped Electron-itg mentioning
confidence: 99%